2020
DOI: 10.1167/iovs.61.5.31
|View full text |Cite
|
Sign up to set email alerts
|

microRNA -378a-3p Restrains the Proliferation of Retinoblastoma Cells but Promotes Apoptosis of Retinoblastoma Cells via Inhibition of FOXG1

Abstract: 378a-3p restrains the proliferation of retinoblastoma cells but promotes apoptosis of retinoblastoma cells via inhibition of FOXG1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(46 reference statements)
0
8
0
Order By: Relevance
“… 39 In contrast, it acted as an tumor suppressor in gastric cancer, 40 colorectal cancer, 41 liver cancer, 42 glioblastoma, 43 prostate cancer, 44 breast cancer (BC), 45 medulloblastoma (MB), 46 pituitary adenoma (PA), 47 oral squamous cell carcinomas, 48 bladder cancer, 49 esophageal carcinoma, 50 rhabdomyosarcoma (RMS), 51 and retinoblastoma (RB). 52 Compared with normal tissues and no lymph node metastasis cancer tissues, miR-378a was upregulated in cervical cancer tissues, especially in CIN III and lymph node metastasis cervical cancer. 33 Additionally, a study of 120 cholangiocarcinoma tissues and adjacent noncancerous tissues found that miR-378a expression increased with the development of the TNM (T-tumor, N-nodes, M-metastasis) stages.…”
Section: Introductionmentioning
confidence: 94%
“… 39 In contrast, it acted as an tumor suppressor in gastric cancer, 40 colorectal cancer, 41 liver cancer, 42 glioblastoma, 43 prostate cancer, 44 breast cancer (BC), 45 medulloblastoma (MB), 46 pituitary adenoma (PA), 47 oral squamous cell carcinomas, 48 bladder cancer, 49 esophageal carcinoma, 50 rhabdomyosarcoma (RMS), 51 and retinoblastoma (RB). 52 Compared with normal tissues and no lymph node metastasis cancer tissues, miR-378a was upregulated in cervical cancer tissues, especially in CIN III and lymph node metastasis cervical cancer. 33 Additionally, a study of 120 cholangiocarcinoma tissues and adjacent noncancerous tissues found that miR-378a expression increased with the development of the TNM (T-tumor, N-nodes, M-metastasis) stages.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have shown that miR-378a-3p is a critical tumor suppressor in multiple cancers, including hepatocellular carcinoma 32 , glioma 33 , and retinoblastoma 34 . However, the function and mechanism of miR-378a-3p in GC have not been thoroughly explored.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-378a-3p, a small noncoding RNA originating from chromosome 5q32, is 22 nt in length. Most studies have reported that miR-378a-3p acts as a tumor suppressor in diverse types of cancers, such as hepatocellular carcinoma 32 , colorectal cancer 45 , esophageal squamous cell carcinoma 46 , ovarian cancer 47 , cervical cancer 48 , retinoblastoma 34 , papillary thyroid cancer 49 , breast cancer 50 , prostate cancer 51 , and glioblastoma 52 . However, miR-378a-3p has also been reported to promote the progression of Burkitt lymphoma 53 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of miR-378a-3p in cell apoptosis remains unclear. Two studies have found that miR-378a-3p promotes the apoptosis of ovarian cancer cells and retinoblastoma cells [ 17 , 23 ]. However, one study demonstrated that miR-378a-3p prevents H9C2 cardiomyocyte cells apoptosis during ischemic injury [ 24 ].…”
Section: Discussionmentioning
confidence: 99%